2018
DOI: 10.17219/acem/78350
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical relation of the extracranial internal carotid artery in the parapharyngeal space

Abstract: Background. The proximity of the internal carotid artery to the pharyngeal wall poses a risk of injury during nasopharyngeal surgery. Objectives. The aim of this study was to assess the distances between the extracranial internal carotid artery (ICA) and the pharyngeal wall. Material and methods. Measurements were taken on certain levels of the pharynx using computed tomography angiography (angio-CT) scans of 97 patients. One-tailed Student's t-test for independent variables and a comparison of expected values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…To evaluate the accuracy of the US estimation, we used CT as a reference method. The CT estimate of the ICA distance from the pharyngeal wall in our participants (mean 20.7 mm, range 14–27) is compatible with the data of Zając et al (mean 19.8 mm, range 10–31) 10 . According to our assessment by the CT, the mean ICA diameter was 4.22 ± 0.63 mm.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To evaluate the accuracy of the US estimation, we used CT as a reference method. The CT estimate of the ICA distance from the pharyngeal wall in our participants (mean 20.7 mm, range 14–27) is compatible with the data of Zając et al (mean 19.8 mm, range 10–31) 10 . According to our assessment by the CT, the mean ICA diameter was 4.22 ± 0.63 mm.…”
Section: Discussionsupporting
confidence: 91%
“…The CT estimate of the ICA distance from the pharyngeal wall in our participants (mean 20.7 mm, range 14-27) is compatible with the data of Zając et al (mean 19.8 mm, range 10-31). 10 According to our assessment by the CT, the mean ICA diameter was 4.22 AE 0.63 mm. Baz et al measured it 4.53 AE 0.50 mm.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the decreased thickness of soft-tissue and muscle layers in females is probably the causative factor of more frequent appearance of ICA anomalies in this group [15]. The Zając's study [31] also states that ICA is closer to the parapharyngeal wall in women then in men but only at the Eustachian tube opening level in nasopharynx. Furthermore, Jun et al [15] found that in nasopharynx and oropharynx, the distance was inversely proportional to the age (p = 0.00).…”
Section: Ica Aberrations and Patients' Characteristicsmentioning
confidence: 83%
“…The mortality rate after tonsillectomy is low, but almost 30% of the deaths are due to bleeding after trauma, due to incision of ICA or external carotid artery and its branches [8]. Therefore, having the knowledge about the variability of ICA in the context of the patient characteristics (for example age, weight [24], gender [15,31]) can be helpful in estimating the risk of arterial injury during tonsillectomy, and thus, reduce post-tonsillectomy mortality. Although many cases of abnormal arterial course were reported in the literature [9][10][11][12][13], only a few of them provided applicative and accurate information about topography of ICA [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main causes of neck artery kinking is the decrease in the height of intervertebral discs due to aging [7]. Also, the results of various studies have shown that the prevalence of kinking in EICA in patients with hypertension has an increasing trend [21,22]. The results of various studies have shown that variations in different parts of the ICA are also found in infants, which are caused by embryological reasons [1,23].…”
Section: Discussionmentioning
confidence: 99%